Benchmarking: An International Journal (Emerald)
Benchmarking: An International Journal (BIJ) is the first journal to examine a business process design and improvement that is revolutionizing established practice and performance and is critical for companies committed to organizational performance based on measures/metrics, benchmarking and implementing the best practices. Its enthusiastic reception by many prominent academic scholars and practitioners have created high levels of interest in benchmarking techniques and best practices which promise improved world class organizational performance.
Keywords: Organizational Performance, Productivity Management, Organisational P2erformance.